Relationships between p53 mutation, HPV status and outcome in oropharyngeal squamous cell carcinoma. Issue 2 (February 2016) - Hong, Angela; Zhang, Xiaoying; Jones, Deanna; Veillard, Anne-Sophie; Zhang, Mei; Martin, Andrew; Lyons, J. Guy; Lee, C. Soon; Rose, Barbara
Abstract: Background and purpose: This study aimed to examine the rate and type of p53 mutation in oropharyngeal cancer (OSCC). Relationships were sought between human papillomavirus (HPV) status and p53 mutation. The role of p53 mutation as a prognostic factor independent of HPV status and as a modifier of the effect of HPV on outcomes was also examined. Methods: The HPV status of 202 cases was determined by HPV DNA by RT-PCR and p16 immunohistochemistry. P53 mutation in exon 5–8 was determined by pyrosequencing. Findings were correlated with known clinicopathological factors and outcomes. Results: 48% of the cases were HPV positive and they were significantly less likely to have a p53 mutation than HPV-negative OSCCs (25.8% vs 46.7%, p = 0.0021). Mutation was most common in exon 5. Among patients with HPV-positive OSCC, there was no significant difference in p53 mutation by smoking status (22.2% for never smokers and 30.8% for current or ex-smokers). Patients with p53 mutant OSCC had significantly worse overall survival ( p = 0.01). There was no statistical evidence that p53 mutation modified the effect of HPV status on outcomes. In the multivariate analysis, positive HPV status remained the strongest predictor of outcomes. p53 mutation status was not a significant predictor of outcome after adjusting for age, gender, T stage, N stage and HPV status. Conclusions: In summary, HPV-positive OSCC are less likely to have mutant p53 than HPV-negative OSCC. Our study did not show any evidence that p53 mutation could modify the effect of HPV status on outcomes.